Shear damping function measurements for branched polymers - Vega, Daniel Alberto (2007)
We present results for step-strain experiments and the resulting damping functions of polyethylene blends of different structures, including solutions of linear, star and comb polymers. Remarkably, an entangled melt of combs exhibits a damping function close to that for entangled linear chains. Diluting the combs with faster-relaxing material leads to a more nearly constant damping function. We find similar behavior for blends of commercial low density polyethylene LDPE. Our results suggest a simple picture: on timescales relevant to typical damping-function experiments, the rheologically active portions of our PE combs as well as commercial LDPE are essentially chain backbones. When strongly entangled, these exhibit the Doi-Edwards damping function; when diluted, the damping function tends toward the result for unentangled chains described by the Rouse model - namely, no damping. © 2007 Wiley Periodicals, Inc.